Evaluation of Chromocult coliform agar for the detection and enumeration of Enterobacteriaceae from faecal samples from healthy subjects - Finney, M.; Smullen, J.; Foster, H.A.; Brokx, S.; Storey, D.M. (Journal of microbiological methods, 2003)
The purpose of this study was to examine the use of Chromocult agar medium for isolation and enumeration of Enterobacteriaceae from human faecal samples, to compare it to MacConkey agar and to evaluate its usefulness as a possible alternative selective medium in human faecal studies. The medium was shown to be effective in identifying Escherichia coli and coliforms in faeces without the need for extensive accompanying biochemical tests for confirmation of identity. A positive correlation ( r=0.86) was found between the recovery of Enterobacteriaceae on the two media, and no significant difference ( P>0.05) between overall mean bacterial counts for the whole study group or at different intervals of faecal collection were observed. Chromocult agar is an effective replacement for MacConkey agar in human faecal studies and has the advantage of differentiating E. coli from other coliforms.